Pengaruh Penerimaan Pajak Daerah Terhadap Pendapatan Asli Daerah Kabupaten Karo - Evida Rahimah; Budiman Rosyadi Nasution; Ujang Abdullah; Subaktiar Subaktiar; Radiah Radiah (Universitas Labuhanbatu, 2023)
Analysis of research to prove whether local tax revenues affect the local revenue (PAD) Karo. The Data used is the annual report of Karo regency during the period 2005-2021, which is published through the website. The method of analysis used in this study is a quantitative method. The results of this study indicate that local tax revenues have a significant effect on the local revenue (PAD) Karo.